Enhancing biomethane potential of pulp and paper sludge through disperser mediated polyhydroxyalkanoates. (1st October 2018) - Sethupathy, A.; Sivashanmugam, P.
Highlights: Extraction time and solvent dosage were optimized for PHAs extraction. The derived PHAs was identified as polyhydroxybutyrate using NMR analysis. PHAs dosage had a significant effect on biomethane production. At 8547 kJ/kg TS, maximum of solubilization rate and SS reduction were achieved. Maximum of biomethane production was achieved by disperser mediated PHAs method. Abstract: In the present study, the extraction of polyester like polyhydroxyalkanoates (PHAs) from enzymes extracted sludge was investigated by varying extraction time and chloroform – sodium hypochlorite dosage. Maximum of 874 mg/g of PHAs was achieved at an optimum extraction time of 120 min and chloroform – sodium hypochlorite dosage of 30% v/v. The characteristics of derived PHAs were examined using Fourier transform infrared (FTIR) spectroscopy and Nuclear magnetic resonance ( 1 H NMR) spectroscopy. Then, the effect of derived PHAs dosage on biomethane production from pulp and paper mill secondary clarifier (PPSC) sludge was studied. Higher amount of biomethane production was observed to be 174 L/(kg VS) at 35 mg of PHAs dosage when compared to other dosage. To further enhance biomethane production, disperser pretreatment method was carried out by optimization of specific energy. At optimum specific energy of 8547 kJ/kg TS, the maximum solubilization rate and suspended solids (SS) reduction were found respectively to be 19% and 15.8%. Then, biomethane assay was conducted on disperser pretreated sludge, disperser pretreated sludge with optimized PHAs dosage (35 mg) and control sludge. Among these, disperser mediated PHAs method exhibited maximal biomethane production and was observed to be 267 L/(kg VS). Hence, PHAs based sludge treatment method can be implemented in sludge management studies by retrieval of value added product and PHAs canbe used to enhance biomethane production sustainably.